2015
DOI: 10.1007/s00417-015-2965-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-term efficacy of subthreshold micropulse yellow laser (577-nm) photocoagulation for chronic central serous chorioretinopathy

Abstract: Subthreshold micropulse yellow laser photocoagulation showed short-term efficacy in treating chronic CSC without retinal damage. However, prospective, randomized, and comparative large-scale studies are needed to evaluate the efficacy and safety of this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 36 publications
3
32
0
1
Order By: Relevance
“…More than 60% of our patients had a disease duration of 41 year. Moreover, some studies show a slightly higher increase in BCVA after SML 17,23 and PDT 13,15,29 compared with our results. This could be attributed to the relatively low BCVA in our patients at baseline.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…More than 60% of our patients had a disease duration of 41 year. Moreover, some studies show a slightly higher increase in BCVA after SML 17,23 and PDT 13,15,29 compared with our results. This could be attributed to the relatively low BCVA in our patients at baseline.…”
Section: Discussionsupporting
confidence: 56%
“…The idea is that retinal damage is not needed to acquire a therapeutic effect. 16 Studies with a 810 nm micropulse diode laser [17][18][19][20][21] and a 577nm micropulse laser 22,23 showed efficacy in CSC patients with subfoveal and extrafoveal leakage sites.…”
Section: Introductionmentioning
confidence: 99%
“…However, the comparison of results between the different investigations is awkward, mainly due to the heterogeneous inclusion criteria, the laser setting and the area of application of the laser spots [33,34,35,36,37,38,39,40,41,42,43]. The studies consider acute CSC forms with symptom durations lasting a few days or less than 1 month as well as chronic forms with a duration range of 3-6 months.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Thus far, the medical literature on the subject concentrates predominantly on discussing the effects of treatment of CSCR. [15,16,17,18,19] Previous authors have suggested varying amounts of reduction of retinal edema and improvement in BCVA; however, the final results usually include cases with insufficient responses to SMPLT-that is, patients with persisting SRF-as well. Moreover, final CRT and BCVA values were not referred to the measurements in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…One of the recent advances in treating CSCR is subthreshold micropulse laser therapy (SMPLT), which is effective in terms of resolution of SRF; however, in CCSCR, this treatment elicits only a moderate improvement of visual acuity. [15,16,17,18,19] Furthermore, the complete resolution of SRF after many months or years of active disease does not necessary mean a restoration of normal vision or normal retinal morphology will occur. To our knowledge, this damage has not yet been precisely assessed in the medical literature; thus, our study sought to evaluate functional and morphological impairments in the retina in long-standing but resolved CCSCR following SMPLT.…”
Section: Introductionmentioning
confidence: 99%